1992
DOI: 10.1136/thx.47.9.755
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long term respiratory damage following inhalation of ammonia.

Abstract: A lifelong non-smoker who was the victim of a massive accidental exposure to anhydrous ammonia gas was followed up for 10 years. In the acute phase the patient presented with severe tracheobronchitis and respiratory failure, caused by very severe burns of the respiratory mucosa. After some improvement he was left with severe and fixed airways obstruction. Isotope studies of mucociliary clearance, computed tomography, and bronchography showed mild bronchiectasis. It is concluded that acute exposure to high conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
7

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 4 publications
0
34
0
7
Order By: Relevance
“…Supportive treatment involves bronchodilators, oxygen therapy, and observation for need for airway protection for 6 to 12 hours as well as early intubation, which may be required to defend the airway from acute laryngeal obstruction. Cricothyroidotomy may be required in more severe cases [4,8,[21][22][23].…”
Section: Ammonia (Nh 3 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Supportive treatment involves bronchodilators, oxygen therapy, and observation for need for airway protection for 6 to 12 hours as well as early intubation, which may be required to defend the airway from acute laryngeal obstruction. Cricothyroidotomy may be required in more severe cases [4,8,[21][22][23].…”
Section: Ammonia (Nh 3 )mentioning
confidence: 99%
“…Its low odor threshold, however, creates an early warning of its presence. Still, olfactory fatigue or adaptation may occur and render its presence less detectable [4,8,[21][22][23].…”
Section: Ammonia (Nh 3 )mentioning
confidence: 99%
“…The extent of respiratory injury after ammonia inhalation depends on the duration of exposure, the concentration of the gas, and the tidal volume. Acute exposure to high concentrations of ammonia may cause tracheobronchitis with severe airflow obstruction followed by chronic airflow obstruction with bronchiectasis (7,8). It has been suggested that long-term exposure to lower concentrations is associated with sinusitis, mucous membrane inflammation syndrome, chronic bronchitis, and asthma-like symptoms (4).…”
mentioning
confidence: 99%
“…Pathological findings include fibrous obliteration of small airways consistent with late stage bronchiolitis obliterans which results in the obstructive component of this disease. 13 …”
Section: Discussionmentioning
confidence: 99%
“…12 Fiberoptic bronchoscopy is helpful for assessment of the inhalational injury as it can reveal erythema, congestion, hemorrhage, and extensive desquamation of the tracheobronchial tree. 13 During the early phase of injury, hypoxemia and acute airway obstruction caused by the sloughing of mucosa pose the greatest threat. When endotracheal intubation is required, the largest possible diameter endotracheal tube should be used because mucosal sloughing may quickly occlude small diameter tubes.…”
Section: Discussionmentioning
confidence: 99%